2022
DOI: 10.1007/s40744-021-00421-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leflunomide on Pegloticase Response Rate in Patients with Uncontrolled Gout: A Retrospective Study

Abstract: Background: Pegloticase, a PEGylated uricase for uncontrolled gout, rapidly lowers serum urate (SU). Not all patients complete a fulltherapy course because anti-pegloticase antibodies can develop, causing efficacy loss and infusion reactions. The literature and clinical trial data indicate that methotrexate co-administration markedly improves pegloticase response rates from the established monotherapy response rate of 42%. Unfortunately, methotrexate use is restricted by kidney disease, which is often present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The 89% response rate reported here is consistent with MIRROR RCT (71% response rate during month 6) [14], an open-label trial with oral MTX (79% response rate during [16], two smaller case series with MTX (both n = 10, 80-100%) [17,18], and a systematic literature review of all immunomodulators (83%) [13]. Another case series (n = 10) showed that leflunomide may also be an option for immunomodulatory cotherapy (70% response rate) [19]. The current study showed a response rate for MMF co-therapy of 100%, but the number of patients administered MMF as co-therapy was small (n = 3).…”
Section: Discussionsupporting
confidence: 87%
“…The 89% response rate reported here is consistent with MIRROR RCT (71% response rate during month 6) [14], an open-label trial with oral MTX (79% response rate during [16], two smaller case series with MTX (both n = 10, 80-100%) [17,18], and a systematic literature review of all immunomodulators (83%) [13]. Another case series (n = 10) showed that leflunomide may also be an option for immunomodulatory cotherapy (70% response rate) [19]. The current study showed a response rate for MMF co-therapy of 100%, but the number of patients administered MMF as co-therapy was small (n = 3).…”
Section: Discussionsupporting
confidence: 87%
“…Given that pegloticase is the only medical therapy indicated for refractory or urate‐lowering therapy–intolerant gout, maximizing the number of patients who achieve sustained lowering of serum urate levels and receive the full course of therapy is extremely important. Preliminary clinical trials (6,7,33) and case series (34–36) in the literature support immunomodulator use in conjunction with pegloticase to increase the proportion of patients with therapeutic response. The MIRROR RCT study, a large, prospective, randomized, placebo‐controlled, double‐blind trial, verified that pegloticase plus oral MTX (15 mg/week) cotherapy resulted in a higher rate of sustained urate lowering than pegloticase plus placebo (pegloticase monotherapy) during the first 6 months of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The literature strongly supports the use of immunomodulation as co-therapy to pegloticase to increase treatment response rates [12] and lower the risk of IRs. [20] Immunomodulatory agents reported in the literature include MTX, [13,15,21,22] mycophenolate mofetil, [23] leflunomide, [17] and azathrioprine, [24] with MTX most studied and now recommended in the updated prescribing information as co-therapy to pegloticase. [25] However, BMI = body mass index, CKD = chronic kidney disease, eGFR = estimated glomerular filtration rate (MDRD equation [18] ), SU = serum urate.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective study examined deidentified real-world case data previously collected for prior retrospective study. [15][16][17] The Western IRB (Puyallup, WA) had reviewed each of those studies, assigning all exempt status. Because all data was existing and de-identified, this study did not meet the definition of human subjects research (NIH tool, https://grants.nih.gov/policy/ humansubjects/research.htm) and further IRB review/approval was not needed.…”
Section: Methodsmentioning
confidence: 99%